2022
DOI: 10.1002/csr.2402
|View full text |Cite
|
Sign up to set email alerts
|

Investigating biodiversity and circular economy disclosure practices: Insights from global firms

Abstract: Business activity has contributed to biodiversity loss. The Circular Economy (CE) system is recommended as a way of recovery and to improve global resilience.Combining accounting and ecology, we examine the intersectionality between biodiversity and CE. Therefore, the research aims to investigate the companies' reporting practices on both CE system implemented, and the corrective actions taken to repair biodiversity. To achieve the research aim, we developed a new disclosure index that includes both biodiversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…For example, our study mainly offers a broad investigation of ESG performance. Some of most specific ESG‐related variables, such as how sustainablility trends (i.e., air pollution (Jiménez‐Parra et al, 2018; Tan et al, 2021), biodiversity risks (Atupola et al, 2023; Roberts et al, 2022), and carbon risks (Doda et al, 2016; Wei et al, 2023)) that affect bid price or target shareholder benefits should be developed in the future studies. In addition, our study mainly investigated in the Chinese market, and given that the different institutional backgrounds of each emerging market have a markedly different effect on corporate investment behavior, other emerging markets should be investigated in the future research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our study mainly offers a broad investigation of ESG performance. Some of most specific ESG‐related variables, such as how sustainablility trends (i.e., air pollution (Jiménez‐Parra et al, 2018; Tan et al, 2021), biodiversity risks (Atupola et al, 2023; Roberts et al, 2022), and carbon risks (Doda et al, 2016; Wei et al, 2023)) that affect bid price or target shareholder benefits should be developed in the future studies. In addition, our study mainly investigated in the Chinese market, and given that the different institutional backgrounds of each emerging market have a markedly different effect on corporate investment behavior, other emerging markets should be investigated in the future research.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Gunarathne et al (2021), by analyzing the integrated and sustainability reports, found that Sri Lankan companies disclose a low level of CE information. Instead, Roberts et al (2023), by examining sustainability and annual reports, found higher CED levels in companies operating in the automotive sector than in those operating in the aerospace and defense sectors. Still focusing on the sustainability and annual reports, Kuo and Chang (2021) examined the determinants and effects of the CED in the Chinese context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have instead jointly examined several types of corporate documents, focusing on the amount of CE information disclosed, the drivers and the effects of the CED (Gunarathne et al, 2021; Kuo & Chang, 2021; Roberts et al, 2023). Specifically, Gunarathne et al (2021), by analyzing the integrated and sustainability reports, found that Sri Lankan companies disclose a low level of CE information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings also revealed that sectors particularly sensitive to institutional pressures are more likely to disclose problems and potential solutions related to their CE projects. Furthermore, Roberts et al (2022) analysed the annual and sustainability reports of companies pertaining to different sectors, observing that those operating in the automotive industry are particularly committed to disclosing CE-related information compared with companies operating in the defence, transportation and aerospace sectors, which are less likely to disseminate CE information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars have investigated companies' CE disclosure practices, examining more types of corporate reports (i.e. García‐Sánchez et al, 2022; Kuo & Chang, 2021; Roberts et al, 2022). Kuo and Chang (2021) examined Chinese companies' CSR and sustainability reports, demonstrating that larger and more environmentally sensitive firms are likely to disclose more CE information to meet stakeholders' expectations.…”
Section: Literature Reviewmentioning
confidence: 99%